Torbulok, Tadschikistan. Ein neuentdecktes Heiligtum im hellenistischen Osten - Lindström, Gunvor (e-Forschungsberichte des DAI, 2023)
In 2008 two large vessels from Torbulok entered the collection of the National Museum of Antiquities in Dushanbe. They could be identified as a perirrhanterion (vessel for ritual purification) and a second cult vessel. Given this the findspot was identified as an ancient sanctuary. Excavations and a survey started in 2013. The archaeological investigation will put another sanctuary on the map of religious sites of the Hellenistic Far East.